Cooperation in combating terrorism in Southern Cone and the challenge of domestic legislation - Ferreira, Marcos Alan Shaikhzadeh Vahdat (Monções: Revista de Relações Internacionais da UFGD, 2014)
This paper aims to analyze the cooperation between Argentina, Brazil and Paraguay in combating terrorism, as well as the challenges that arise with the different domestic legislation about terrorist threat. According to some analysts and by the United States, the two 1990s attacks occurred in Buenos Aires, created the perception of the region as a possible financial safe haven of international terrorism. After 9/11 attacks the region has increased the cooperation in combating terrorism, nonetheless the countries maintained different laws towards this threat. The paper evidences the necessity of a common perception to combating terrorism, especially considering that the region will host two important events in the next years: the Olympic Summer Games 2016 and FIFA World Cup 2014.